Development of Monopoly Games on Organisms Classification Material at VII Grade to Increase Motivation Learning - Isna, Isnanik Juni Fitriyah; Yusi Saputri, Wan Eka (Educational Researcher Journal, 2025)
Learning media that are less innovative and varied can result in reduced student learning motivation. One of the learning media that can be used is monopoly game. The research aims to determine the development, practicality, and effectiveness of the SIMAHI Monopoly game to increase learning motivation. This is development research with the ADDIE model which consists of analysis, design, development, implementation and evaluation. This research is a pre-experimental study with a one group pretest-posttest research design. Data collection was carried out by interviews and questionnaires. The data analysis used in this study was the prerequisite test (normality and homogeneity) and paired t-test. The results of this study indicate that the monopoly game is feasible to use with media validation of 80.88% and material validation of 93.85%, both of which are in the very valid category. For practicality the teacher gets 97.50% and students 85.98% including the very practical category. The SIMAHI monopoly game is effective for increasing learning motivation with a percentage of 11.19%. The results of the t-test show that there is a significant difference in average between students' learning motivation before and after using the SIMAHI Monopoly game learning media.